Migration, Household Tasks, and Gender: Evidence from the Republic of Georgia1. Issue 2 (23rd March 2015) - Torosyan, Karine; Gerber, Theodore P.; Goñalons‐Pons, Pilar
Abstract : We examine whether migration affects the gender division of household tasks and participation in leisure within origin‐country households using survey data from the Republic of Georgia. Our theoretical framework identifies two sets of mechanisms whereby migration might influence gender differences in home activities: migrant experience effects and migrant absence effects. We test for both types of effects on the probability that men and women perform gender atypical household tasks and engage in leisure activities by comparing households with and without currently absent and return migrants using probit regressions. We find evidence for both migration absence and migration experience effects on gender differences in housework and leisure. However, these effects are complex and contradictory: Generally, male migration tends to exacerbate gender differences in the sending household while female migration tends to ameliorate them.